A triple iron triathlon leads to a decrease in total body mass but not to dehydration - Knechtle, B.; Knechtle, P.; Rosemann, T.; Oliver, S. (Research Quarterly for Exercise and Sport, 2010)
A loss in total body mass during an ultraendurance performance is usually attributed to dehydration. We identified the changes in total body mass, fat mass, skeletal muscle mass, and selected markers of hydration status in 31 male nonprofessional ultratriathletes participating in a Triple Iron triathlon involving 11.4 km swimming, 540 km cycling and 126.6 km running. Measurements were taken prior to starting the race and after arrival at the finish line. Total body mass decreased by 1.66 kg (SD = 1.92; -5.3 kg to +1.2 kg; p < .001), skeletal muscle mass by 1.00 kg (SD = 0.90; -2.54 kg to +2.07 kg; p < .001), and fat mass by 0.58 kg (SD = 0.78; -1.74 kg to +0.87 kg; p < .001). The decrease in total body mass was associated with the decrease in skeletal muscle mass (r = .44; p < .05) and fat mass (r = .51; p < .05). Total body water and urinary specific gravity did not significantly change. Plasma urea increased significantly (p < .001); the decrease in skeletal muscle mass and the increase in plasma urea were associated (r = .39; p < .05). We conclude that completing a Triple Iron triathlon leads to decreased total body mass due to reduced fat mass and skeletal muscle mass but not to dehydration. The association of decrease in skeletal muscle mass and increased plasma urea suggests a loss in skeletal muscle mass.